Элементы теории светорассеяния и оптическая локация - Орлов В. М.; Самохвалов И. В.; Матвиенко Г. Г.; Белов М. Л.; Орлов В. М. Владимир Михайлович (Новосибирск, Наука, 1982)
Авт. указаны на обороте тит. л.